Rancang Bangun Sistem Optimasi Penggunaan Bahan Baku Dengan Metode Simpleks - Pratama, I Putu Adi; Prasetya Hogantara, Kadek Anggie (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Maximizing profit is a key objective for companies, particularly in industries with production constraints. Republic of Soap, a soap manufacturing company, faces challenges in optimizing its production process due to limited raw materials. The company produces soaps in three variants: 40 grams, 100 grams, and 125 grams. Given the limitations of available raw materials, this study proposes an optimization system to determine the maximum achievable profit. By implementing the Simplex algorithm, the proposed system calculates the optimal allocation of raw materials to maximize profits. The results show that the optimal production plan involves 20.20 batches of 40-gram soap, yielding a total profit of IDR 4,251,151.52. System testing confirmed the ability of the optimization model to generate optimal profits, demonstrating its effectiveness in supporting decision-making for raw material utilization in production. This research provides a valuable approach to addressing production constraints while enhancing profitability.